Multi‑frequency CMOS oscillator based on CMOS MEMS SAW resonator - Karim, Jamilah; Zainuddin, Ahmad Anwar; Alam, A. H. M. Zahirul; Nordin, Anis Nurashikin (Springer Berlin Heidelberg, 2015)
This paper presents the design and simulation results for a multi-frequency oscillator based on complementary metal oxide semiconductor (CMOS) microelectromechanical systems (MEMS) surface acoustic wave (SAW) resonator. Multi-frequency oscillator is simulated using 0.35 μm CMOS technology. The oscillator operated at 600 and 1.76 GHz. The multi-frequency oscillator shows phase noise performance of −67.35 and −92.83 dBc/Hz at 100 kHz offset frequency for 600 MHz and 1.76 GHz, respectively, during simulation. The pierce circuit topology was used to sustain the oscillation from CMOS SAW resonator. The sustaining circuit was design and fabricated in 0.35 μm CMOS technology process with 3.3 V supply. The measured S21 of sustaining circuit topology are 6 and 2 dB at 1.76 GHz and 600 MHz, respectively. The phase responses for 1.76 GHz and 600 MHz are −50° and –200° correspondingly.